Effects of different-valent vaccines against human papillomavirus (HPV) to prevent persistent HPV16/18 infections and CIN2+ in women: a systematic review and network meta-analysis - Haiyue Wu; Lucia Li; Kun Fu; YuFei Shen; Yingnan Lu; Zexi Liao; Yingzhen Liu; Wenting Zha; Lisha Wu; Yu Zhang (International Journal of Infectious Diseases)
Objectives: To evaluate the efficacy of 2-valent, 4-valent and 9-valent HPV vaccination in preventing persistent HPV infections and cervical intraepithelial neoplasia grade 2 or higher (CIN2+) lesions among women with different infection statuses at baseline. Methods: PubMed, Web of Science, Cochrane, Embase and ClinicalTrials.gov were searched from their inception to March 2024. Randomized controlled trials (RCTs) and post hoc analyses of RCTs reporting the risk of persistent HPV infections and CIN2+ among vaccinated women were included. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to summarize the intervention effects. Results: Eighteen RCTs and one post hoc analysis of RCTs were included. In the according-to-protocol (ATP) cohorts, the 4-valent vaccine was the most effective against HPV16/18-related persistent infections and CIN2+ (6-month persistent infections (6mPIs): OR 0.05, 95% CI [0.02, 0.15]; 12-month persistent infections (12mPIs): OR 0.02, 95% CI [0.00, 0.18]; CIN2+: OR 0.03 95% CI [0.01, 0.17]). For the total vaccination cohorts (TVCs), the 2-valent vaccine was most effective against HPV16/18-related 12mPIs and CIN2+ (12mPIs: OR 0.15, 95% CI [0.04, 0.63]; CIN2+: OR 0.52 95% CI [0.32, 0.87]), whereas the 4-valent vaccine was most effective against HPV16/18-related 6mPIs (OR 0.08, 95% CI [0.02, 0.28]). Conclusions: Vaccination against HPV can significantly reduce the risk of persistent HPV16/18-related infections and CIN2+, regardless of the HPV infection prevaccination. In addition to 4- and 9-valent vaccines, 2-valent vaccines could also provide satisfactory protection against persistent HPV16/18-related infections and CIN2+, especially over the long term, and may constitute an alternative for government-led vaccination programs in developing countries.